Basic principles of international protection of the marine environment: Selected aspects of law, doctrine and policy - Łukaszuk, Leonard (Studia Ecologiae et Bioethicae, 2006)
The author of this article presents the notion and meaning of international protection of the marine environment and offers a solid legal and philosophical background to this issue. He points at and systematically analyzes a kind of compendium of selected main legal and philosophical principles as environmental values, included in the United Nations Convention on the law of the sea (1982). The author discusses both environmental management at seas as a global system and topical issues in the light of international legal instruments, doctrine, and some practical experiences. He also shows the environmental law as an increasingly important area of new interdisciplinary study and addresses how this law and science may best able to address the key issues facing the marine environment in the 21st century.